Parental Responsibilities Towards Children Who Do Begging Activities in Gorontalo City - Abdul Rahman Suleman (Estudiante Law Journal, 2020)
This study aims to determine and analyze the responsibilities of parents in employingchildren as beggars and to determine the purpose of Islamic law and civil law on parentalresponsibilities. The type of research used is empirical research, namely research that includes legalidentification and research on legal effectiveness. The results of the study show that the basis ofparental responsibility in employing children as beggars in Gorontalo City is an error in the soul ofparents concerning their behavior in this case employing children as beggars who can be sanctioned.Based on his psyche, the perpetrator can be reproached because of his behavior, in other words, onlywith this inner connection can the prohibited act be held accountable for the parents who employtheir children as beggars. In Islam, the law of begging has been explained that the law is not allowed.What is recommended is that it is better to give each other the hand above than the hand below.Keywords: Parents Responsibility, Child Labour, Beggar